Development with Identity: Development Policy in a Multiethnic State Nepal - Prakash Rai (Prāgyik Prabāha, 2024)
The concept of development with identity also termed ethno-development refers to development policies that are sensitive to the needs of indigenous people and ethnic minorities. It is the opposite concept of the ethnocidal strategy of development. As the then prime minister of Nepal KP. Sharma Oli proclaimed that the government would destroy the huge stone in the Saptakoshi / Koshi as it hindered the steamship on its way in a public program in Biratnagar, people from Kirati community, one of the groups of indigenous nationalities of Nepal, opposed the assertion and launched a series of protest programs since the huge stone has been supposed to be a mythically historical stone for them. This event raised the issue of ethno-development. In this article, I have argued that the Eurocentric and purely economy-centric development practices have created the condition of conflict rather than cohesion in the multiethnic country since social, civilizational, and cultural dimensions of the people are entirely ignored by this practice. Therefore, development with identity is an appropriate policy of development for a country like Nepal having diversity in terms of civilization, ethnicity, culture, and language. I have adopted in-depth interviews based on the qualitative approach in this research.